Salinity Sensor Development for Pond Water Utilizing Ultrasonic Wave - Dananjaya Endi Pratama; Agus Indra Gunawan; Rusminto Tjatur Widodo; Akhmad Hendriawan (Politeknik Kelautan dan Perikanan Dumai, 2022)
Shrimp farming is one of the most popular aquaculture activities in Indonesia. This activity is carried out in a pond. Therefore, there are many ponds as a place for shrimp farming in Indonesia. Several factors affect the results of shrimp farming in ponds. One of the factors is water quality. Four parameters that are commonly used to indicate water quality i.e. dissolve oxygen, salinity, PH, and temperature. In this study, we discussed salinity measurement. Most salinity sensors use the probe principle in measurement. When the sensors are used to measure the water that contains mineral salts, the probe will be susceptible to rust and cause measurement errors. Based on these conditions, we conducted a study of salinity measurements by using the acoustic technique. The measurement was carried out by using an ultrasonic wave. The water salinity was determined based on the acoustic intensity and acoustic speed. In this research, we developed a conversion curve based on the measurement of acoustic intensity from NaCl, KCl, and MgCl2 saline solutions with certain concentrations. The conversion curve is used to measure salinity in pond water. We also calculated salinity based on the measurement result of acoustic speed. From the experiment, the NaCl conversion curve became the most suitable for salinity measurement. The measurement result of salinity in pond water from the NaCl saline solution conversion curve was very close to the results of Del Grosso formula, Chen Millero formula, and refractometer.